PERBEDAAN BAHASA MELAYU PONTIANAK KALIMANTAN BARAT DENGAN BAHASA INDONESIA STANDAR - Erick Prasetyo Dwi Putra; Umi Hartati (CARAKA, 2016)
The research aims to (1) describe the difference of Pontianak Malayan of west Borneo with Indonesiansâ€™ standard according to phonologic and (2) describing the difference of Pontianak Malayan of west Borneoâ€™s vocabulary with Indonesiansâ€™ standard. This research used a qualitative method that focuses on showing the meaning, describing, purification, placement of data on the context. The data source was 200 of Pontianak Malayan of west Borneoâ€™s vocabulary based on Swadesh lists that translate in Indonesian. The instrument of this research was a recorder that used to interview some native inhabitants of Pontianak of west Borneo which have Pontianak Malayan of west Borneo accent. Then the researcher saw the difference of Pontianak Malayan of west Borneo with Indonesian made in written type. The researcher used â€œSimak methodâ€, recording, interview, and taking note. The researcher used Padan method in this research. The method used in the research is shown by informal. The result of the research are (1) of Pontianak Malayan of west Borneo with Indonesiansâ€™ standard according to phonologic including (a) regular difference they are [a]-[âˆ‚], [i]-[Îµ], [u]-[O], [r]-[k], [Ã˜]-[k], (b) irregular difference they are [l]-[k], [k]-[g], [i]-[a], (2) difference of Pontianak Malayan of west Borneoâ€™s vocabulary with Indonesiansâ€™ standard, there are 21 vocabularies.